Choosing between what you want now and what you want most: Self-control explains academic achievement beyond cognitive ability. (May 2016) - Stadler, Matthias; Aust, Miriam; Becker, Nicolas; Niepel, Christoph; Greiff, Samuel
Abstract: Achieving a university degree is a demanding long-term goal, and students often show varying levels of academic achievement despite similar intellectual abilities. In order to help students, researchers thereby need to understand the origins of these individual differences. However, it remains unclear whether self-control is important for students' academic achievement beyond their general cognitive ability. To answer this question, N = 150 German university students completed a measure of general cognitive ability as well as a German translation of the Brief Self-Control Scale. Grade point average (GPA) served as an objective indicator of academic achievement, complemented by personal ratings as a measure of subjective academic achievement (SAA). Both cognitive ability and self-control explained substantial amounts of variance in GPA; however, only self-control accounted for variance in SAA. The study's key finding was that self-control indeed contributed to explaining GPA and SAA, even when cognitive ability was controlled for. On the basis of these results, we argue that self-control holds important explanatory value for both objective and subjective academic achievement, and we discuss the results' practical relevance with regard to student success at university. Highlights: We investigated the value of self-control in the prediction of academic achievement. Academic achievement was operationalized as GPA and subjective academic achievement. Self-control predicted both objective and subjective academic achievements.